2014
DOI: 10.3389/fpls.2014.00501
|View full text |Cite
|
Sign up to set email alerts
|

Resource competition in plant invasions: emerging patterns and research needs

Abstract: Invasions by alien plants provide a unique opportunity to examine competitive interactions among plants. While resource competition has long been regarded as a major mechanism responsible for successful invasions, given a well-known capacity for many invaders to become dominant and reduce plant diversity in the invaded communities, few studies have measured resource competition directly or have assessed its importance relative to that of other mechanisms, at different stages of an invasion process. Here, we re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
252
2
14

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 329 publications
(298 citation statements)
references
References 314 publications
6
252
2
14
Order By: Relevance
“…Indirect effects have also been examined to improve our understanding of the efficacy of the use of v www.esajournals.org biocontrol agents to control invasive populations, with studies showing that the presence of alternative hosts decreased the effectiveness of biological control, while increasing the richness of a particular guild of natural enemies can reduce the density of a widespread group of herbivorous pests and increase crop yields (Cardinale et al 2003). Overall, the importance of indirect interactions relative to direct interactions, such as resource competition, in promoting successful invasions is largely unknown (Gioria andOsborne 2014, but see Palladini and. Additional studies are required to examine the role of indirect interactions in promoting plant invasions and how indirect effects may be manipulated to control plant invasions.…”
Section: Discussionmentioning
confidence: 99%
“…Indirect effects have also been examined to improve our understanding of the efficacy of the use of v www.esajournals.org biocontrol agents to control invasive populations, with studies showing that the presence of alternative hosts decreased the effectiveness of biological control, while increasing the richness of a particular guild of natural enemies can reduce the density of a widespread group of herbivorous pests and increase crop yields (Cardinale et al 2003). Overall, the importance of indirect interactions relative to direct interactions, such as resource competition, in promoting successful invasions is largely unknown (Gioria andOsborne 2014, but see Palladini and. Additional studies are required to examine the role of indirect interactions in promoting plant invasions and how indirect effects may be manipulated to control plant invasions.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the ability to tolerate a low nitrogen environment is essential to the strong competitive ability of R. pseudoacacia (Boring & Swank 1984a;Gioria & Osborne 2014), and is a main reason why R. pseudoacacia is considered to be a good invasive species itself outside of its native range in the eastern USA (Castro-DĂ­ez et al 2008). The comparatively small size of A. altissima seedlings in this study suggested that the nutrient levels used may have been too low for A. altissima to thrive in a sandy environment.…”
Section: 2mentioning
confidence: 99%
“…Some researchers suggest that the superior competitive ability of invasive species over native species is closely related to more efficient resource acquisition or resource conservation (Tecco et al 2010;Gioria & Osborne 2014). A variety of invasive species have higher resource-use efficiency than native species, especially in low-resource environments (Funk & Vitousek 2007).…”
Section: The Presence Of a Altissima Inhibited Nodulation Of R Pseumentioning
confidence: 99%
“…However, in studies concerning relationships between invasive and native species, authors frequently focused only on competition between the alien and native species, and intraspecific competition, neglecting relationships between two invaders (e.g., Mangla et al 2011;RodrĂ­guez-EcheverrĂ­a et al 2013). Studies concerning relationships between two alien species are relatively rare, but essential to better understanding the competitive interactions among alien species, and increase our knowledge of secondary invasions (Gioria and Osborne 2014). It is especially important when occurrence of earlier-established invaders modifies environments in ways which facilitate dispersal distance of secondary alien species, according to the invasional meltdown concept (Simberloff and Von Holle 1999;Simberloff 2006;Gioria et al 2011).…”
Section: Introductionmentioning
confidence: 99%